Tatwiri ad-Darama li Ta’limi Maharati al-Kalam - Dian Risky Amalia; Miatin Rachmawati; Zughrofiyatun Najah; Dara Maya Sari (Jurnal Internasional Pendidikan Bahasa Arab, 2021)
This study aims to determine the process of formulating the drama method and its effectiveness to improve speaking skills in second semester students majoring in English Education at IAIM Metro Lampung. This study used an experimental procedure where the researcher conducted a pre-test and post-test on 2 groups (control and experiment). The population of this study were second semester students majoring in English Education at IAIM Metro with a total of 20 children, consisting of 10 children for the control group and 10 children for the experimental group.This study aims to determine the process of formulating the drama method and its effectiveness to improve speaking skills in second semester students majoring in English Education at IAIM Metro Lampung. This study used an experimental procedure where the researcher conducted a pre-test and post-test on 2 groups (control and experiment). The population of this study were second semester students majoring in English Education at IAIM Metro with a total of 20 children, consisting of 10 children for the control group and 10 children for the experimental group. The results of this study are: 1) the process of preparing the drama method to improve speaking skills at IAIM Metro Lampung requires perseverance and thoroughness with the following steps: 1-Preliminary analysis,2- Product preparation,3- Product validation,4- Product revision ,5-Product trial, 6-Design revision, 7-Product production at the final stage. 2) The average score for the control group that did not use the drama method was 53.9, while the experimental group that used the drama method was 58.4. From the results of these values, the researchers calculated to with the results of 2,482 while the t value in (t-table) with a significance level of 5% was 2.10. Then it can be seen that the calculated t value is higher than the t-table value (2,482 > 2,10). With the conclusion that the use of the drama method can improve learning speaking skills in semester 2 IAIM Metro Lampung students.